Rút gọn biểu thức\(B=\frac{x^{39} x^{36} x^{33} ... x^3 1}{x^{40} x^{38} x^{36} ... x^2 1}\)\(A=\frac{x^{95} x^{94} x^{93} ... x 1}{x^{31} x^{30} x^{29} ... x 1}\)
Rút gọn biểu thức
\(B=\frac{x^{39}+x^{36}+x^{33}+...+x^3+1}{x^{40}+x^{38}+x^{36}+...+x^2+1}\)
\(A=\frac{x^{95}+x^{94}+x^{93}+...+x+1}{x^{31}+x^{30}+x^{29}+...+x+1}\)
\(\left(\frac{x+1}{39}+1\right)+\left(\frac{x+2}{38}+1\right)=\left(\frac{x+3}{37}+1\right)+\left(\frac{x+4}{36}+1\right)\)
Cho đa thức f(x)=\(\left(x^2+x+2\right)^{20}\)=\(a_0x^{40}+a_1x^{39}+a_2x^{38}+...+a_{39}x+a_{40}\)
Tính \(S=a_0+a_1+a_2+...+a_{39}+a_{40}\)
+) KHÔNG DÙNG MÁY TÍNH.HÃY TÍNH NHANH GIÁ TRỊ CỦA BIỂU THỨC SAU:
\(40^2-39^2+38^2-37^2+...+2^2-1^2\)
+) TÌM x , BIẾT:
\((3x-1)^2+2(x+3)^2+11(x+1)(1-x)=6\)
giải phương trình
a)x-13/33 +x-21/29 +x/25 = 0
b) (x-69)/30 + (x-67) /32 +(x-65)/34 =(x-63)/36 +(x-61)/38 +(x-59)/40
giải phương trình
a)x-13/33 +x-21/29 +x/25 = 0
b) (x-69)/30 + (x-67) /32 +(x-65)/34 =(x-63)/36 +(x-61)/38 +(x-59)/40
giải phương trình
a)x-13/33 +x-21/29 +x/25 = 0
b) (x-69)/30 + (x-67) /32 +(x-65)/34 =(x-63)/36 +(x-61)/38 +(x-59)/40
\(\frac{392-x}{32}+\frac{390-x}{34}+\frac{388-x}{36}+\frac{386-x}{38}+\frac{384-x}{40}=-5\)
Tim x